1987
DOI: 10.1073/pnas.84.8.2391
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of mitochondrial and chloroplast genomes in crosses of Chlamydomonas.

Abstract: Physical differences between organelle genomes of the interfertile species Chlamydomonas reinharodt and Chlamydomonas smithii have been used to demonstrate that sexual zygotes transmit chloroplast and mitochondrial DNA from opposite mating types. Processes responsible can be separated functionally and genetically, although both are controlled by mating type. In vegetative diploids, chloroplast and mitochondrial genomes are transmitted biparentally, but a 1-kilobase insert present in the C. smithy mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(69 citation statements)
references
References 30 publications
2
67
0
Order By: Relevance
“…On the other hand, the evidence of mtDNA complementation and recombination clearly indicates that mitochondrial fusion does occur in other organisms, such as S. cerevisiae (10), Chlamydomonas spp. (6), and plants (39,46). However, it has also been found in yeast cells that, in p+ x p+ crosses, mtDNA mixing is not extensive and appears to be limited to that portion of the zygote which gives rise to medial buds and, furthermore, that the sorting of mtDNA is controlled differently from that of the bulk matrix protein constituents (3).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the evidence of mtDNA complementation and recombination clearly indicates that mitochondrial fusion does occur in other organisms, such as S. cerevisiae (10), Chlamydomonas spp. (6), and plants (39,46). However, it has also been found in yeast cells that, in p+ x p+ crosses, mtDNA mixing is not extensive and appears to be limited to that portion of the zygote which gives rise to medial buds and, furthermore, that the sorting of mtDNA is controlled differently from that of the bulk matrix protein constituents (3).…”
Section: Discussionmentioning
confidence: 99%
“…The null growth phenotype of these mutants under heterotrophic conditions was inherited by the mating type minus parent, a characteristic of a genetic lesion located in the mitochondrial genome [42].…”
Section: Genetics Of Chlamydomonas To Isolate Respiratory-deficient Mmentioning
confidence: 99%
“…Boynton et al (1987) Whether the mt+ or mt-parent carried the mutation, the diploids showed a paternal inheritance frequency of between 100 and 56%, depending on the experiment. Thus, the vegetative diploids showed biparental mtDNA inheritance.…”
Section: No Methylation Of Mtdnamentioning
confidence: 99%
“…Experiments showing the paternal inheritance of mtDNA in Chlamydomonas Boynton et al (1987) crossed interspecific strains of C. smithii mt+ with C. reinhardtii mt-and analyzed the resulting progeny based on physical differences in restriction fragment patterns between the organelle genomes of these strains. A reciprocal cross was also conducted.…”
Section: Chlamydomonasmentioning
confidence: 99%